Conceptual-methodological proposal between sustainable management and agricultural business Competitiveness - Ruiz Rodriguez, Rosmery (2021)
The complexity derived from integrating sustainability with competitiveness and the economic nature of the current development system is a challenge, but it also represents the opportunity to rethink various concepts that allow the incorporation of innovations in agricultural companies. The present research aims to propose the concept of competitive sustainable management, a methodological classification and analysis of the concept, which supports its empirical contribution. The methodology used consists of the analysis of the concepts of competitiveness and sustainability, from the approach of the management concept as a juxtaposition agent between them; The dimensions of sustainability were identified, aligning the characteristics of competitiveness to categorize both concepts and define in measurement indicators a way to describe the generation of competitive advantages and sustainability inserted in the agricultural business environment.